Granice nowego dramatu serbskiego — płynne i stale wytyczane na nowo. Perspektywa lokalna i recepcja w Polsce - Abrasowicz, Gabriela (Przekłady Literatur Słowiańskich, 2020)
Since the turn of the millennium, Serbian drama has been increasingly valued and recognized in the post-Yugoslav region and in Europe. In recent years, the process of globalization has become progressively stronger, with an improved infrastructure for promotion that has made possible the crossing of material and symbolic boundaries. This in turn has led to transformations in artistic expression, as well as increasing opportunities for mobility, co-productions, and translations. The status of the drama has been somewhat problematic because of its situation between literature and theatre. Its heterogeneous nature has required the development of an appropriate method of presentation. The performative/stage reading has emerged as a compelling answer.